2017
DOI: 10.1098/rsbl.2016.0797
|View full text |Cite
|
Sign up to set email alerts
|

Ocean acidification alters predator behaviour and reduces predation rate

Abstract: A contribution to the special feature 'Ocean acidification'. Ocean acidification poses a range of threats to marine invertebrates; however, the emerging and likely widespread effects of rising carbon dioxide (CO 2 ) levels on marine invertebrate behaviour are still little understood. Here, we show that ocean acidification alters and impairs key ecological behaviours of the predatory cone snail Conus marmoreus. Projected nearfuture seawater CO 2 levels (975 matm) increased activity in this coral reef molluscivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…This study demonstrates that there are similar behavioural effects of elevated CO 2 on two separate cephalopod orders that occupy largely distinct niches, and that these effects are consistent with those seen in a range of other taxa (Allan et al., ; Pistevos et al., ; Watson et al., ). The similar effects of elevated CO 2 on both species seen here indicates potential for a variety of cephalopods to be adversely affected, with possible consequences for a diversity of marine habitats and ecosystems.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study demonstrates that there are similar behavioural effects of elevated CO 2 on two separate cephalopod orders that occupy largely distinct niches, and that these effects are consistent with those seen in a range of other taxa (Allan et al., ; Pistevos et al., ; Watson et al., ). The similar effects of elevated CO 2 on both species seen here indicates potential for a variety of cephalopods to be adversely affected, with possible consequences for a diversity of marine habitats and ecosystems.…”
Section: Discussionsupporting
confidence: 82%
“…In the jumping conch snail, elevated CO 2 affects predator‐escape behaviour, reducing the proportion of snails that jump from a predator, and increasing the latency to jump, as well as altering the escape trajectories of snails that do jump to escape predation (Watson et al., ). More recently elevated CO 2 has been shown to cause a reduction in the predation rates of the predatory marbled cone snail; 60% of control snails successfully captured and consumed their prey compared with 10% at elevated CO 2 , despite a threefold increase in activity levels at elevated CO 2 (Watson, Fields, & Munday, ). To date, studies on the potential effects of elevated CO 2 on more advanced and active molluscs, such as cephalopods, have largely focused on physiological traits.…”
Section: Introductionmentioning
confidence: 99%
“…Increased sea surface temperatures have already affected the metabolism, behaviour, phenology and distribution of species across a range of taxa (Scheffer et al 2001, Johansen et al 2014, Byrne et al 2017, Pecl et al 2017. Ocean acidification (OA) -altered seawater chemistry as a result of uptake of atmospheric CO 2 emissions -is also predicted to alter the growth, calcification, reproduction and behaviour of many marine species (Langdon et al 2000, Ross et al 2011, Byrne et al 2013, Watson et al 2017. Ocean warming and acidification are both increasing at unprecedented rates (IPCC 2014), hence understanding their combined impacts on the performance and growth of marine organisms will be key to predicting future changes in marine communities (Byrne 2011, Przeslawski et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the 0.1 to 0.4 drop in pH, projected to occur by 2100 (i.e., a greater than 30% increase in acidity, Orr et al 2005, Meehl et al 2007, IPCC 2014 has been shown to reduce growth and survival in key ecosystem species with calcifying structures (Orr et al 2005), e.g., temperate sea urchins that help control algae growth on reefs (Dupont et al 2010); reef-building corals and calcareous algae (Hoegh-Guldberg et al 2017), and reef-inhabiting sea stars that regulate the diversity, distribution and abundance of their prey (Dupont et al 2010). Also, increased CO2 levels impair behaviors in predator-prey interactions in tropical gastropods , Watson et al 2017, coral reef fishes (Munday et al 2009b, Dixson et al 2010, and tropical squid (Spady et al 2014).…”
Section: List Of Figuresmentioning
confidence: 99%